(untitled) (AmS-Skrifter, 2020)
While most of this volume’s contributions trace Hanseatic influences throughout the North Atlantic, this paper examines a possible counter-influence in the shape of a medieval shipwreck discovered in Bremen in 2007, the construction of which is reminiscent of the Scandinavian shipbuilding tradition. With its radially cleft planks, inlaid wool caulking and clinkerfastenings, the wreck displays a number of features that point typologically to a vernacular Scandinavian origin. However, the planks fall into two groups outside of Scandinavia: high quality wainscot planks cut in the Baltic region in the course of the fourteenth century, and a group of locally cut timber — arguably for repairs — dating from the second quarter of the fifteenth century. This period coincides with a peak of Baltic timber export, especially wainscot for shipbuilders. Hence, the wreck is discussed within the wider context of clinker-built wrecks from this period in general and wrecks built of Baltic oak in particular.